PATHOGENETIC IMPORTANCE OF INTRAMITOCHONDRIAL OXIDATIVE MECHANISM IN CONDITIONS OF EXPERIMENTAL ACUTE PYELONEPHRITIS COMPLICATED BY HYPERGLYCEMIA - Borisov S.О.; Kostev, F.I.; Borisov, O.V.; Mikheytseva, I.N.; Kolomiichuk, S.G.; Tiron, O.I. (World of Medicine and Biology, 2024)
The purpose of the study was to determine the oxidative stress pathogenetic role in the kidney mitochondria energy metabolism disorders progress in conditions of acute experimental pyelonephritis complicated by hyperglycaemia and study of the drug impact in these metabolic disorders. Acute pyelonephritis alone and being complicated by a hyperglycemic state reproducing diabetes mellitus I and II types were modeled in rats. Rats with acute pyelonephritis complicated by diabetes mellitus I and II type received both etiotropic drug influence and etiopathogenetic drug influence for 14 days. The activity of prooxidant (NADPH-oxidase and xanthineoxidase) and mitochondrial enzymes cytochromeoxidase and adenosinetriphosphatase were studied in kidneys of rats 28 days after the trial start. The comorbid hyperglycemic state on the background of acute pyelonephritis contributes to rats’ kidneys metabolic disorders progress associated with oxidative stress further development against the background of mitochondria energy metabolism disorders. The use of etiopathogenetic drug influence, in contrast to etiotropic drug influence, has a positive impact on prooxidant enzymes activities cytochromeoxidase and adenosinetriphosphatase in kidneys of rats with acute pyelonephritis complicated by diabetes mellitus I and II type. A pathogenetically important link in acute pyelonephritis complicated manifestation is the presence of a concomitant hyperglycemic state with the development of mitochondrial dysfunction in kidney cells and oxidative stress. The data of the study is an experimental background of etiopathogenetic drug influence reasonability in complex therapy of patients with acute pyelonephritis with concomitant diabetes mellitus.